2006
DOI: 10.1073/pnas.0510391103
|View full text |Cite
|
Sign up to set email alerts
|

Muscle GLUT4 regulation by estrogen receptors ERβ and ERα

Abstract: Estrogen is known to influence glucose homeostasis with dominant effects in the liver, but the role of estrogen receptors in muscle glucose metabolism is unknown. In the present study, we investigated the expression of the two estrogen receptors, ERα and ERβ, and their influence on regulation of the glucose transporter, GLUT4, and its associated structural protein, caveolin-1, in mouse gastrocnemius muscle. Immunohistochemical analysis revealed that ERα and ERβ are coexpressed in the nuclei of most muscle cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
184
3
11

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 237 publications
(207 citation statements)
references
References 29 publications
8
184
3
11
Order By: Relevance
“…ER␣ and ER␤ were detected in tissue sections by standard immunofluorescence as described in ref. 42. For immunofluorescent detection, 4-m paraffin sections were dewaxed in xylene and rehydrated through graded ethanol to water.…”
Section: Methodsmentioning
confidence: 99%
“…ER␣ and ER␤ were detected in tissue sections by standard immunofluorescence as described in ref. 42. For immunofluorescent detection, 4-m paraffin sections were dewaxed in xylene and rehydrated through graded ethanol to water.…”
Section: Methodsmentioning
confidence: 99%
“…Pellets were dissolved in SDS sample buffer, and the proteins were resolved by SDSpolyacrylamide gel electrophoresis with 4-20% gradient gels (Invitrogen, Carlsbad, CA, USA) as described before. 42,43 After transfer to PVDF membranes (Applied Biosystems, Foster City, CA, USA), blots were probed with anti-ERbLBD antibody, followed by appropriate secondary antibodies conjugated with horseradish peroxidase. Detection was by enhanced chemiluminescence ECL kit (Amersham Pharmacia, Pittsburgh, PA, USA).…”
Section: Western Blottingmentioning
confidence: 99%
“…In women with gestational diabetes mellitus, however, the problem regarding tissue insulin sensitivity is restricted to post-binding steps, such as reduced tyrosine kinase activity, decreased expression of insulin receptor substrate-1 (IRS-1) and increased levels of the p85α subunit of PI 3-kinase (Barbour et al 2007). Interestingly, estrogens have been implicated in changes in insulin secretion, and also in reduced insulin sensitivity and glucose tolerance, especially in muscles (Godsland 2005, Barros et al 2006. Batista et al (2005) showed that chronic exposure of bitches to estradiol and progesterone causes insulin resistance in the whole body, but primarily in the skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%